Quasi experimental study of same-sex marriage laws & sexually transmitted infections - Ammar Aftab; Sara Imanpour (Elsevier, 2022)
Objectives: On June 26, 2015, the Supreme Court legalized same-sex marriages in the United States. This change has had some positive implications for the health of Lesbian, gay, bisexual, and transgender (LGBT) individuals and public health in general. Sexually transmitted infections (STIs) are common among LGBT individuals and legalization of same sex marriage effected the rate of emergency department (ED) visits for STIs. We examined the effect of same-sex marriage legalization on emergency department visits related to STIs among LGBT individuals. Study design: Quasi-experimental difference-in-difference negative binomial design is used with state and time fixed-effects. We used data for 16 states from State Emergency Department Database and State Inpatient Database from January 2007-December 2015. People over 18 years of age visited the ED for STIs were included. Results: At 5% significance level, number of STIs cases decreased by 6.1% (95% CI, 0.906-0.973; P = 0.001) after same-sex marriage legalization. When adjusting for sex, these cases decreased by 7.6% (95% CI, 0.885-0.966; P < 0.001) for females, and 4.7% (95% CI, 0.914-0.995; P = 0.027) for males. By age cohorts, 18-24 aged had 8.5% (95% CI, 0.875-0.957; P < 0.001) decrease, while older age cohorts was statistically insignificant. Conclusions: Our results show that there is an association between legalization and decreased STIs cases in ED visits. Policy makers need to focus on encouraging a positive attitude towards LGBT community, as it leads to better quality of health for sexual minority groups and leads to positive externalities for general community.